Target zones for the US dollar? - Wolfgang Filc (Intereconomics, 1986)
The discussion of target zones for flexible exchange rates is evidence of the desire to experiment with new instruments for stabilising the international monetary system. What distinguishes target zones from systems of flexible and fixed exchange rates? What form should they take? How should one regard the various objections to target zones?
Keywords: 330; Monetary Policy